Tonsing, B. K., "The Quakers in South Africa: a social witness" - Guiton, Gerard (Quaker studies, 2004)
Tonsing, B. K., The Quakers in South Africa: a social witness (Series in Quaker Studies,Vol. 3), L ewiston: The Edwin Mellen Press, 2002. pp. v + 354, ISBN 0 7734 7104 9, Cloth, £74.95,$ 119.95.